Microfluidic Electrochemical Desalination Systems: A Review - Abuwatfa, Waad (2025)
Microfluidic techniques have emerged as promising, efficient, cost-effective, and environmentally friendly desalination solutions. By utilizing fluid dynamics at the microscale, these techniques offer precise control over chemical, biological, and physical processes, presenting advantages such as reduced energy consumption, miniaturization, portability, and enhanced process control. A significant challenge in scaling microfluidic desalination for macro applications is the disparity in flow rates. Current devices operate at microliters per minute, while practical applications require liters daily. Solutions involve integrating multiple units on a single chip and developing stackable chip designs. Innovative designs, such as 3D microfluidic chips, have shown promise in enhancing scalability. Fouling, particularly in seawater environments, presents another major challenge. Addressing fouling through advanced materials, including graphene and nanomaterials, is critical to improving the efficiency and longevity of devices. Advances in microfluidic device fabrication, such as photo-patterned hydrogel membranes and 3D printing, have increased device complexity and affordability. Hybrid fabrication approaches could further enhance membrane quality and efficiency. Energy consumption remains a concern, necessitating research into more energy-efficient designs and integration with renewable energy sources. This paper explores various electrochemical-based microfluidic desalination methods, including dialysis/electrodialysis, capacitive deionization (CDI)/electrochemical capacitive deionization (ECDI), ion concentration polarization (ICP), and electrochemical desalination (ECD).